A comparison study on patient-reported outcome between obese and non-obese patients with central lumbar spinal stenosis undergoing surgical decompression: 14,984 patients in the National Swedish Quality Registry for Spine Surgery - Niyaz Hareni; Kari Gudlaugsson; Fredrik Strömqvist; Björn E Rosengren; Magnus K Karlsson (Acta Orthopaedica, 2022)
Background and purpose: Obesity has been associated with inferior outcomes after laminectomy due to central lumbar spinal stenosis (CLSS); we evaluated whether this occurs in surgery on national bases. Patients and methods: We retrieved pre- and 1-year postoperative data from the National Swedish Quality Registry for Spine Surgery regarding patients aged ≥ 50 with laminectomy due to CLSS in 2005–2018. 4,069 patients had normal weight, 7,044 were overweight, 3,377 had class I obesity, 577 class II obesity, and 94 class III obesity (“morbid obesity”). Patient-reported outcome included satisfaction after 1 year, leg pain (Numerical Rating Scale [NRS], rating 0–10), disability (Oswestry Disability Index [ODI], rating 0–100). Complications were also retrieved. Results: 1-year postoperatively, 69% of patient of normal weight, 67% who were overweight, and 62% with obesity (classes I–III aggregated) were satisfied (p < 0.001) and 62%, 60%, and 57% in obese groups I–III, respectively (p = 0.7). NRS leg pain improved in normal-weight patients by 3.5 (95% CI 3.4–3.6), overweight by 3.2 (CI 3.1–3.2), and obese by 2.6 (CI 2.5–2.7), and 2.8 (CI 2.7–2.9), 2.5 (CI 2.2–2.7), and 2.6 (CI 2.0–3.2) in obese classes I–III, respectively. ODI improved in normal weight by 19 (CI 19–20), overweight by 17 (CI 17–18), and obese by 14 (CI 13–15), and 16 (CI 15–17), 14 (CI 13–16), 14 (CI 11–18) in obese classes I–III, respectively. 8.1% of normal weight, 7.0% of overweight, and 8.1% of obese patients suffered complications (p = 0.04) and 8.1%, 7.0%, and 17% among obese classes I–III, respectively (p < 0.01). Conclusion: Most obese patients are satisfied after laminectomy due to CLSS, even if satisfaction rate is inferior compared with normal-weight patients. The morbidly obese have more complications than patients with lower BMI.